A percepção de agricultores e de outros agentes rurais acerca das dimensões ambiental, social e econômica no cultivo de tabaco no município de Arvorezinha (RS). - Troian, Alessandra (2010)
The recognition that smoking is a global problem meant that States Members of the United Nations to propose the adoption of the first international treaty of public health. This is the Framework Convention on Tobacco Control (FCTC), whose main objective is to stop the spread of smoking and its damage to health (INCA 2004). From this convention are emerging worldwide and country questions about the sustainability of the cultivation of tobacco, as well as strong criticism by environmental problems triggered in the relationship established producer/ integrators. Thus, the central objective of this study is to evaluate qualitatively the perceptions of farmers and other rural stakeholders about the environmental, social and economic cultivation of tobacco in the city of Arvorezinha (RS). Whereas to meet this objective, the quantitative data cannot explain some questions about the cultivation of tobacco, it is sought through qualitative techniques to reveal such perceptions. The main techniques used in the study were semi-structured interviews, participant observation and field notebook, and the stage of literature review. The results show that there are many different perceptions in the field of study. It was evident that the main concern of the respondents is directed to the economic aspect, which is also the main motivation for farmers to grow tobacco. In general, farmers have some environmental perceptions, among which stands out the care of the land and the maintenance and expansion of wildlife. As perceptions about health, they range from the belief in immunity to acceptance of the problem caused by the planting of tobacco and its subsequent consumption. About the technical assistance, in general the perceptions are disparate. There are farmers who feel the need for assistance and others who regard the system of technical assistance efficient. When it comes to environmental legislation it is perceived that farmers have, some fear, from the agencies that execute the laws, some because of this preserve natural resources, others anyway risk and "escape" from the legislation. The Perceptions about the FCTC politics shows that farmers and rural actors don t know the measure. It is not something that has been discussed at day-to-day of the involved in the production chain of local tobacco. Finally we can consider that, although many farmers are unhappy with the cultivation of tobacco, there are many difficulties and limitations to replace it. Among the barriers to replace the cultivation of tobacco, the respondents cite the geographical and agro-ecological properties, the lack of capital for investment, the need for technical assistance and the know to do. It should be considered that is not intend of this study concluding the discussion about the perception of the cultivation of tobacco, but it aims to help ensure that new studies emerge to broaden the debate on the issue. It is necessary also make reference that is a case study limited in space, time and place.